Evaluasi Penerapan Hiradc Sebagai Upaya Pencegahan Risiko Kecelakaan Kerja Pada Kegiatan Housekeeping Area Workshop Fabrikasi Di PT. XYZ - Siti Nurhaidah Kholisah (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
Housekeeping activities in the fabrication workshop area are crucial to ensure tidiness, cleanliness, and work safety. However, these activities still present risks that can cause work accidents if not handled properly. The problem in this study lies in the mismatch between the Hazard Identification, Risk Assessment, and Determination of Control (HIRADC) document and the actual implementation in the field of housekeeping activities in the PT. XYZ fabrication workshop. As a solution, the implementation of the HIRADC method is very important to identify hazards, assess potential risks, and determine appropriate control measures. The purpose of this study is to assess the implementation of HIRADC as an effort to prevent the risk of work accidents in housekeeping activities in the PT. XYZ fabrication workshop. The method used in this study is a descriptive evaluative approach with data collection techniques including field observations, interviews, document studies, and checklists to evaluate the implementation of HIRADC. The research findings indicate that most potential hazards have been detected in the HIRADC document, including the risk of slipping, being hit by material, and injuries due to the use of work tools. The identified risk levels vary from low to high, with the percentage of implementation compliance reaching 73.7%. However, discrepancies remain regarding the consistency of risk control implementation, document updates, and field supervision. Therefore, improved oversight, regular document updates, and ongoing evaluation are needed to make workplace accident prevention efforts more effective.